Enhancement of Reversing Effect of Cyclosporin A on Vincristine Resistance by Anti‐P‐glycoprotein Monoclonal Antibody MRK‐16 - Naito, Mikihiko (Jpn J Cancer Res, 1993)
The synergistic effect of MRK‐16, a monoclonal antibody against P‐glycoprotein, and cyclosporin A (CsA) on the modulation of vincristine resistance was studied by isobologram analysis in three different, highly multidrug‐rcsistant tumor cells. In all cell lines, the synergistic effect was demonstrated at various concentrations of MRK‐16 and CsA. While MRK‐16 alone did not enhance the sensitivity of the moderately resistant KB‐8–5 cells to vincristine, it increased two‐fold the reversing effect of cyclosporin A at 1 μM, an achievable blood concentration. Since MRK‐16 alone showed therapeutic effects against multidrug‐resistant tumors, the combined use of MRK‐16, CsA and antitumor agents should provide therapeutic benefits for the treatment of resistant tumors.